The Influence of Inpatient Service Quality on Patients' Decisions to Go Home at Their Own Request (Paps) at The Mayjen H.A Thalib Regional Hospital, Sungai Penuh City - Putri, Puji Audina; Romauli Anna Teresia Marbun; Tati Murni Karokaro (JURNAL KESMAS DAN GIZI (JKG), 2025)
"Discharge at Own Request (PAPS)" is one of the indicators used to assess the quality of inpatient care services. Based on direct interviews with several PAPS patients in the inpatient ward of a particular regional public hospital (RSUD), several factors were identified as triggers for their decision to leave, including the waiting time for treatment and the condition of the treatment room and walls, which appeared uncomfortable—especially for patients who did not yet have a BPJS National Health Insurance) card.The high incidence of patients discharging themselves at their own request (PAPS) has an impact on the hospital, including a potential decrease in service efficiency, as indicated by a reduction in the length of stay (LOS). This study aims to identify and analyze the influence of inpatient service quality on the decision of patients to discharge themselves at their own request (PAPS) at RSUD Mayjen H.A. Thalib, Sungai Penuh City, in 2025.This is a quantitative study using a cross-sectional study design. The research was conducted at RSUD Mayjen H.A. Thalib, Sungai Penuh City, from November 2024 to April 2025. The sample consisted of 125 patients hospitalized in the inpatient ward of RSUD Mayjen H.A. Thalib, Sungai Penuh City. The sampling technique used was accidental sampling.The research findings indicate a correlation between patient satisfaction—based on the aspects of tangibles, reliability, Responsiveness , assurance, and empathy—and the decision to discharge themselves at their own request (PAPS) at RSUD Mayjen H.A. Thalib, Sungai Penuh City, in 2025. Therefore, it is recommended that regular training be provided to all medical personnel and hospital staff to enhance their competence and ability to deliver optimal healthcare services.